Cassava breeding and varietal dissemination in India: Major achievements during the past 25-30 years - Abraham, K.; Nair, S.G.; Naskar, S.K. (International Center for Tropical Agriculture, 2001)
Cassava (Manihot esculenta Crantz) has been grown in India for more than a century. Although cassava breeding was initiated during the 1940s in Kerala, intensive research on breeding of superior varieties began only after the establishment of the Central Tuber Crops Research Institute (CTCRI) in 1963 in Trivandrum, Kerala. The Institute has an immense wealth of cassava germplasm, both indigenous and exotic. Nine superior varieties were released by CTCRI, three of them developed by selection, five by intervarietal hybridization and one by triploidy breeding. The high yielding hybrids not only increased cassava cultivation but also spread the crop outside Kerala. At present cassava is cultivated in 12 states and two union territories of the country, but the major producer is Kerala followed by the neighboring states of Tamil Nadu and Andhra Pradesh. The hybrids H-226 and H-165 are the most popular varieties in the industrial areas of Tamil Nadu and Andhra Pradesh, but the recently released triploid hybrid ‘Sree Harsha’, with its high yield, high starch and good culinary quality, holds great potential for both industrial use and human consumption. The three short-duration varieties are highly preferred by farmers as a rotation crop in the paddy-based cropping system. Very recently, two superior top-cross hybrids, having high yield and good culinary quality, were developed from in breds and are ready for formal release. In recent years the spread of cassava outside Kerala has been quite substantial. In Tamil Nadu and Andra Pradesh, where cassava is mainly used as an industrial crop for starch and sago manufacture, cassava area and production are expanding. In the northeastern states, where it is used mainly as a food crop, cultivation is also gradually increasing. In non-traditional areas of central India, the crop is being introduced through the true seed program. Nevertheless, the total area and production of cassava in India is declining, especially in Kerala, due to the prominence gained by plantation crops like rubber, black pepper, coffee etc. which provide more cash income. Therefore, the future increase in cassava production seems possible only by increasing the productivity in the existing areas of cultivation, expanding its adoption in different cropping systems and introducing the crop to new, non-traditional areas. To fulfil this goal, a new challenge in cassava breeding would be the development of gene pools with adaptation to the main biological and physical environmental stresses, development of varieties having resistance to CMD and red mite as well as drought tolerance, the nutritional improvement of cassava roots by protein enrichment, as well as the development of high-yielding, high-starch and high eating-quality hybrids, which will be acceptable to farmers, processors and consumers. Among the conventional breeding techniques, triploidy and top crossing are probably better tools for this. However, biotechnological approaches through gene transfer might tackle the challenges in a shorter time, but this will require coordinated research efforts among international and national agricultural institutions.